KEBUTUHAN BELAJAR IBU RUMAH TANGGA USIA SUBUR DI DESA SIPUNGGUK KECAMATAN SALO KABUPATEN KAMPAR - Hayati, Padilah; Irja, Desti; Natuna, Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on needs learn housewives fertile in village Sipungguk Kecamatan Salo Kabupaten Kampar. Needs learn housewives is the or enterprise undertaken for research and find things needed in learning that can be seen from; (a) needs learning pertaining to a work assignment; (b) needs learn that deals with fondness and recreation; (c) needs learn pertaining to religious; (d) needs learn that deals with a mastery of language and general knowledge; (e) needs learn pertaining to a tanggaan; (f) needs learn pertaining to penamilan self; (g) needs learn that deals with knowledge tourism; (h) needs learning related to the efforts in agriculture; (i) needs learn pertaining to services. Formulation problems research is whether needs learn housewives fertile in the village Sipungguk Kecamatan Salo Kabupaten Kampar?. The purpose of this research is to find the study housewives fertile in the village Sipungguk Kecamatan Salo Kabupaten Kampar. Population in this study as many as 75 people .Then the researcher take intended to the sample 43 people to research and 20 people to test on using a technique simple random sampling. An instrument data collection namely poll with 62 a statement and if the trial live 60 a statement that valid to make instrument in research. Through data analysis of the quantitative descriptive analysis. So, a conclusion can be drawn, needs learn housewives fertile in the village Sipungguk Kecamatan Salo Kabupaten Kampar sub indicators to 9 sub indicators in know its mean value and primary schools high.Key words: Needs Learn, Needs Learn Housewives Fertile